Endoscopic banding ligation compared with sclerotherapy for the treatment of espohageal varices - Ahmet DOBRUCALI; Kadir BAL; Murat TUNCER; Feryal İLKOVA and Aykut ÇELİK and Hülya UZUNİSMAİL and; him YURDAKUL and Ergun OKTAY (Turkish Journal of Gastroenterology, 2019)
-